Approaches to the problems of political risk in foreign direct investment - Howard, Christopher O (Department of Political Studies, 2016)
This thesis examines the challenges multinational enterprises face from political risk when making and operating foreign direct investments. The thesis considers political risk and a wide variety of approaches to its analysis and provides insight into the process of foreign direct investment, the nature of the political threat facing it, foreign investment decision making by multinationals, and the tools developed in the commercial, academic, and governmental arenas to avoid and combat the effects of political risk. In essence, the thesis addresses a business application of theories and methodologies used in political studies. The first hypothesis is: if political risk is properly understood as a phenomenon of the political environment, then it a) defies direct quantification and b) can be explained as a series of discrete elements which can be analyzed separately. The second hypothesis is: if political risk is properly understood as a series of non-quantifiable elements, analysis of political risk cannot be depended upon alone to protect multinational enterprises from political risk in foreign direct investment. The first hypothesis is addressed through a critical review and consideration of business and political risk literature. Two analytical tools are developed in this process: a ladder of cognition consisting of a series of conditions of knowledge which can be held regarding a specific risk, and indicating the type and approximate accuracy of analysis which can be undertaken of such risk; and a representation of the political risk equation as a two stage process consisting of an abstract (environmental) risk event and a discrete effect which the event may or may not have on a specific investment. The second hypothesis is addressed through a critical review of methods of political risk analysis including "qualitative" approaches with roots in traditional studies and "quantitative" approaches derived from statistical analysis and behavioralist-based determinism. Critiques of each approach include operational strengths and weaknesses, performance histories (when applicable), conceptual and practical capabilities from the perspective of the analytical tools described above, and theoretical strengths and weaknesses from the perspective of the political studies discipline. Both hypotheses are supported and the thesis concludes by reviewing tools which can be used by multinationals to manage and mitigate the effects of political risk and considering additional academic work in this arena which would be useful in developing this application of political studies.